Parasites of domestic and wild animals in South Africa. LI. Ticks infesting leopard tortoises Stigmochelys pardalis, hingeback tortoises Kinixys zombensis and angulate tortoises Chersina angulata - Horak, Ivan G. (Onderstepoort J Vet Res, 2017)
The objective of the study was to record the tick species collected from three species of tortoise, each in a different province of South Africa. Ticks were collected from leopard tortoises, Stigmochyles pardalis, in the southern region of the Kruger National Park, Mpumalanga province; from hingeback tortoises, Kinixys zombensis, in the Enseleni Nature Reserve, KwaZulu-Natal province and from angulate tortoises, Chersina angulata, in the West Coast National Park, Western Cape province. Of the 63 leopard tortoises examined, 58 were infested with Amblyomma marmoreum and 49 with Amblyomma hebraeum, and all stages of development of both species were recovered. Amblyomma nuttalli was collected from 25 hingeback tortoises, and all stages of development were present. All 24 angulate tortoises examined were infested with Amblyomma sylvaticum, and large numbers of larvae, nymphs and adults were collected. Three snake species and a sand lizard were also infested with A. sylvaticum. The adults of A. marmoreum, A. nuttalli and A. sylvaticum were identified as specific parasites of the family Testudinidae, whereas all stages of development of A. hebraeum were classified as generalists.